UWARUNKOWANIA I ZAŁOŻENIA SYSTEMU SŁUŻB OCHRONY ZABYTKÓW W POLSCE - Bogusław Szmygin (Ochrona Dziedzictwa Kulturowego, 2016)
Since 1989, the system of monument protection in Poland has been adapting to the changes occurring in the Polish political system. Defining the scope of power and duties of historic preservation services is not only a tremendously important element of these changes. It is also a key factor in how the monument protection system functions. The nature of the changes results in stakeholders playing increasingly significant role in protection of monuments and sites – they become major partners to historic preservation services. Moreover, these services may find regional government bodies having broad scope of duties pertaining to monument protection particularly useful. Increasing significance of the role that local government bodies have been playing results in the scope of power and duties of regional historic preservation offices being broadened. Local government bodies are therefore going to participate more actively in the protection of historic monuments and sites. At the same time, their actions should be inspired, planned, and coordinated by regional historic preservation services. Support and supervision, on the other hand, should be provided by state historic preservation service being independent of local government bodies. The state and local government services cannot be therefore considered an alternative – they should fully and closely cooperate with each other. For this reason, cooperation among these services should be promoted and encouraged.